GENERAL LOGIC TEXTS IN THE COLLEGE LEVEL IN PERU - Vásquez Tasayco, Alberto (2014)
The teaching and learning of general logic at the university level, from 1940 to the present, shows a decrease in its importance in training. In 1946, Francisco Miro Quesada said that is because it is ascribed to positivism. However, the same Luis Miro Quesada and then Piscoya, Diogenes Rosales and Oscar Trelles assume responsibility for publishing texts of general logic, nationwide. This situation is driven by the publication of texts at the secondary level to support the philosophy course (and Logic), which establishes the Peruvian educational system. At the university level, each text has its advantages in various fields and are still the most used in our country. The most concerned is Miro Quesada, text also has published more titles with complementary logical issues, then the largest circulation published text is Diogenes Rosales, first alone, then coauthored with Oscar Trelles. Finally, Luis Piscoya published a book containing theoretical foundations issues in Logic and Logic basic operations general.